Outlook web app : online with Office 365 - Walsh, Heather; Safari eBooks ([Place of publication not identified] : CompuWorks, 2016)
"This course is designed to be an overview of using Microsoft's Outlook Web App. Students will learn how to perform many of the functions that are also located in the Desktop version of Microsoft Outlook such as, reading and responding to emails, creating and formatting messages, managing the mailbox, creating folders for organization, and printing emails. Students will learn to automate Outlook Web App with Rules, Action Items. They will learn to manage the Calendar, and create appointments and meetings, and work with Contacts and Tasks. Additionally, students will learn how to navigate the Office 365 Mail environment and new features and differences of using Outlook in the cloud."--Resource description page.
Title from resource description page (viewed August 26, 2016).
Presenter, Heather Walsh.
Keywords: Microsoft Outlook; Electronic mail systems; Electronic books